HQE²R - an European assessment tool towards sustainable neighbourhoods - Holger Martin; Andreas Blum (European Regional Science Association (ERSA), 2002)
The Institute of Ecological and Regional Development (IOER) is the German contractor of "Sustainable Renovation of Buildings for Sustainable Neighbourhoods" (HQE²R - Haute Qualité Environnementale et Economique Réhabilitation), partially funded by the EC under the Fifth Framework Programme. The project started in July 2001 and will continue until December 2003. Coordinated by CSTB France (Centre Scientifique et Technique du Bâtiment) it combines research and demonstration aspects by cooperation of nine European partners in connection with 15 international case studies. The project's objective is to develop a new methodology and the necessary tools to promote sustainable development and quality of life on the crucial and likewise challenging level of urban neighbourhoods. HQE²R will be a decision support tool for municipalities and their local partners, focussing on the aims of inhabitants and users of neighbourhoods. In its integrated approach it is meant to be generally applicable in Europe. The project is using the case studies as model neighbourhoods for the methodology to be provided. In Germany the case study will be carried out in Dresden-Loebtau. Loebtau residential area is a traditional workers quarter, cut off from the city-centre by large roads, railroad infrastructure and extensive brownfield sites. Although renovation works have been supported by declaring districts as "rehabilitation areas", Loebtau is facing a high residential vacancy. The challenge is how the considerable success in renovations achieved on building scale can be extended into sustainable neighbourhood development. Main targets therefore are to identify urban development measures towards sustainable development, especially in socio-economic terms and to find an appropriate methodology to estimate or assess the environmental effects arising from different combinations of socio-economic, urban planning and urban infrastructure measures.At ERSA 2002 we would be glad to present the methodology of neighbourhood analysis developed within the HQE²R project. The approach will be demonstrated by the case study of Dresden-Loebtau, showing how the application of the instrument has been carried out in practice. Furthermore the assessment and decision support tool to improve the quality of measures towards a sustainable neighbourhood can be presented in its state of the art, at this time still being under development.
Keywords: 330